2020
DOI: 10.1007/s00248-020-01643-1
|View full text |Cite
|
Sign up to set email alerts
|

A Generalist Lifestyle Allows Rare Gardnerella spp. to Persist at Low Levels in the Vaginal Microbiome

Abstract: Gardnerella spp. are considered a hallmark of bacterial vaginosis, a dysbiosis of the vaginal microbiome. There are four cpn60 sequence-based subgroups within the genus (A, B, C and D), and thirteen genome species have been defined recently. Gardnerella spp. co-occur in the vaginal microbiome with varying abundance, and these patterns are shaped by a resourcedependent, exploitative competition, which affects the growth rate of subgroups A, B and C negatively. The growth rate of rarely abundant subgroup D, howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…Factors like generalist lifestyle, social cheating, and bet hedging, can contribute to the selection of rare genotypes [8,9,[16][17][18][19][20]. It has been shown that rarely abundant Gardnerella subgroup D are nutritional generalists [8], which may help them to be favoured by negative frequency-dependent selection. However, the fact that subgroup D has not been observed to dominate the vaginal microbiome begs the question: if rare subgroup D is favoured by negative frequency-dependent selection, why do not we see microbiomes dominated by subgroup D more often?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors like generalist lifestyle, social cheating, and bet hedging, can contribute to the selection of rare genotypes [8,9,[16][17][18][19][20]. It has been shown that rarely abundant Gardnerella subgroup D are nutritional generalists [8], which may help them to be favoured by negative frequency-dependent selection. However, the fact that subgroup D has not been observed to dominate the vaginal microbiome begs the question: if rare subgroup D is favoured by negative frequency-dependent selection, why do not we see microbiomes dominated by subgroup D more often?…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously studies that the rare Gardnerella species (subgroup D) have minimal overlap with the other Gardnerella spp. and are probably occupying a different niche in the vagina [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative frequency-dependent selection favours rare genotypes [1,2]. Factors like generalist lifestyle, social cheating and bet hedging can contribute to the selection of rare genotypes [8,9,[16][17][18][19][20]. It has been shown that rarely abundant Gardnerella subgroup D are nutritional generalists [8], which may help them to be favoured by negative frequency-dependent selection.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup D isolates were subsequently shown to have a nutritional generalist lifestyle and limited niche overlap with other Gardnerella spp. suggesting that these isolates persist in the vaginal microbiome through negative frequencydependent selection [8]. Vaginal microbiomes dominated by subgroup D, however, have not been reported [6,7].…”
Section: Introductionmentioning
confidence: 95%